Linking analytics data and digital systems for supporting cognition and exploratory learning in 21st Century - Ifenthaler, D.; Sampson, Demetrios; Spector, J. (Elsevier, 2018)
© 2017 Elsevier Ltd Technology-supported learning environments generate vast amount of data from learners and/or educators interactions, that can be collected and analyzed through pedagogically relevant algorithms producing even more data from these aggregations. The link between available educational data, methods for their analysis, and relevant technologies for incorporating educational data analytics in digital learning environment, are globally investigated for their potential to transform learning, teaching, and assessment towards offering unique and personalized learning experiences to the 21st century learners. Thus, research on Linking Analytics Data and Digital Systems for supporting Cognition and Exploratory Learning in 21st Century aims to contribute to the global dialogue between the educational technology and educational psychology research communities and the educational practitioners on current issues towards large scale take-up of educational technologies.